Basic Occupational Health Services for Agricultural Workers in the South of Iran. Issue 3 (31st August 2018) - Tabibi, Ramin; Tarahomi, Shahram; Ebrahimi, Seyed Mohammad; Valipour, Ali-Asghar; Ghorbani-Kalkhajeh, Sasan; Tajzadeh, Shokat; Panahi, Davood; Soltani, Shahrzad; Dzhsupov, Kenesh O.; Sokooti, Maryam
The agricultural sector has by far the world's largest labour force, there are more than one billion workers in this industry worldwide, which contains half of the total world labour force. On the other hand, agriculture is one of the most hazardous occupations, and many workers suffer occupational accidents and ill health each year. Farming and animal breeding are associated with exposure to a wide variety of risk factors, including zoonotic agents, dust, elements of the thermal environment, noise, vibration and chemicals. Although half of the world's population are economically active and spend at least one third of their time in the workplace, only 15% of the workers have access to basic occupational health services. According to a WHO report, Iran has a well-structured health care system through which basic health care services are available to the entire population, and health indicators in Iran have consistently improved. The agricultural health program in Iran is being carried out in the cities and rural areas, and occupational health services are mainly integrated into the health network. This paper aims to describe the health care system and basic occupational health services (BOHs) available to 5, 300 agricultural enterprises with 8, 380 employees in the cities of Abadan, Khorramshahr and Shadegan in the Abadan region (Abadan, Khoramshahr and Shadegan districts), in the south of Iran.